[TEX]\left{\begin{xy+x+1=7y(1)}\\{x^2y^2+xy+1=13y^2(2)} [/TEX]
ta thấy y =0 hệ thành x= -1
1=0 => y=0 ko phải là nghiệm của pt
với y # 0 ta chia 2 vế pt (1) cho y và pt ( 2) cho [TEX]y^2[/TEX]
=> hệ thành [TEX]\left{\begin{x+\frac{x}{y}+\frac{1}{y}=7(3)}\\{x^2+\frac{x}{y}+\frac{1}{y^2}=13(4)}[/TEX]
đặt [TEX]u=x+\frac{1}{y}[/TEX]
[TEX]v=\frac{x}{y}[/TEX]
[TEX]=>u^2=x^2+\frac{1}{y^2}+2v[/TEX]
hệ thành [TEX]\left{\begin{u+v=7(5)}\\{u^2-v=13(6)} [/TEX]
từ pt (5) suy ra v = 7-u
\
thế vào pt (6) [TEX]=>u^2-(7-u)=13[/TEX]
<=>[TEX]u^2+u-20=0[/TEX]
<=> u=4 hoặc u=-5
. u=4 => v=3 => hệ [TEX]\left{\begin{x+1/y=4}\\{x/y=3} [/TEX]
=> x= 1=> y = 1/3 hoặc x = 3 => y=1
. u=-5 => v = 12 => hệ [TEX]\left{\begin{x+1/y=-5}\\{x/y=12} [/TEX]
=> PTVN
vậy S={ (1,1/3), ( 3,1) }